ChemInform Abstract: Carbon—Carbon Bond Forming Reactions via Photogenerated Intermediates. Issue 47 (3rd November 2016) - Ravelli, Davide; Protti, Stefano; Fagnoni, Maurizio
Abstract: Review: 485 refs.